SUSTAINABILITY REPORTING: STAKEHOLDER PRESSURE AND BOARD COMPOSITION INFLUENCE - Evy Steelyana W; Kevin Michael Kusuma Raharjo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research examines how stakeholder pressure and board characteristics influence the quality of sustainability reporting among Indonesian firms listed on the Indonesia Stock Exchange between 2016 and 2020. Through an analysis of 30 companies over a five-year period, we utilize linear regression to explore the relationship between board size, board education, shareholder pressure, creditor pressure, and sustainability report quality. Our findings suggest that while board size has no significant impact on sustainability reporting quality, board education plays a positive and significant role, aligning with Upper Echelons Theory. Additionally, shareholder pressure is positively associated with report quality, indicating investor interest in non-financial disclosures. Conversely, creditor pressure does not significantly affect report quality, suggesting a focus on debt repayment over CSR disclosures. These findings underscore the importance of knowledgeable board leadership and stakeholder engagement in driving high-quality sustainability reporting, offering insights for further research into industry-specific dynamics and board composition characteristics.